UPAYA PENERAPAN DIVERSIFIKSI PANGAN TERHADAP MEWUJUDKAN INDONESIA TANPA IMPOR BERAS - ITA ROS ITA (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
ABSTRACTThis research is motivated by the high number of rice imports by Indonesia. The method used in this study uses description research methods. Food diversification is an effort to invite people to diversify staple foods so that they are not focused on just one type. Diversification itself is closely related to food security, where this is an effort or effort to realize food security for Indonesia. Rice is biologically part of the rice seed which consists of an embryo which is a candidate for a new plant (in rice it cannot grow again, except with the help of tissue culture techniques). The content of rice itself consists of carbohydrates which are the main component in rice. The habits of the Indonesian people who cannot be separated from rice, make rice a crucial item that cannot be replaced. This fact makes Indonesia increasingly dependent on rice imports. The purpose of this research is to make efforts to implement food diversification so that it does not focus only on rice as the main food commodity.